Lessons from forest rehabilitation through agroforestry trials in lowland Kutai, East Kalimantan, Indonesia - Toma, T. (ASEAN-Korea Environmental Cooperation Project (AKECOP), 2003)
The eastern part of Kutai Regency (lowland Kutai) in East Kalimantan, Indonesia is susceptible to large-scale wildfires during severe droughts related to strong El Nino Southern Oscillation (ENSO) events as shown by the 1982-83 and 1997-98 fires. Since the 1982-83 forest fires, many trials have been conducted to rehabilitate the burned forests. However, the 1998 fires burned those rehabilitated forests in lowland Kutai. It is expected that severe droughts related to strong ENSO events and subsequent wildfires will occur again in the near future. Without effective fire prevention, the rehabilitated areas will be burned again and the rehabilitation process will never have enough time to reach completion. To rehabilitate burned forests and grasslands, it is important that community-based initiatives be undertaken to reduce potential fire sources and to enhance fire management activities. Clear benefits to the local community should be introduced and announced to the local people before and during forest rehabilitation. In this context, agroforestry systems will be keys to rehabilitate the degraded forest lands in such a fire prone region. The possibilities and constraints of forest rehabilitation through agroforestry in lowland Kutai are discussed based on the lessons learnt from the past initiatives conducted in the region.